Forests and floods - MIN, Kyonggi (KDI School, 2022)
This paper conducts the empirical analysis of the relationship between forest stock and flood damage based on the Republic of Korea’s national reforestation program (1973-1987). Reconstructing the historical forest statistics of Korea Forest Service and expanding Seo’s (2018) dataset, I capitalize on a growing stock by forest types to examine whether coniferous, deciduous and mixed forests reduced flood damage. From a fixed-effect analysis, my results show that not all types of forests reduce flood damage. I find that coniferous or deciduous forests did not have a mitigation effect on flood damage, whereas mixed forests did. These results may reflect to the lack of a forest management policy and a coniferous-oriented reforestation program in Korea. From the results, this paper suggests that even if reforestation was successful, it might not lessen flood damage if forest management is not appropriately initiated after reforestation. Furthermore, deciduous forests should be adequately planted when one expects afforestation to ease flood damage.
Thesis(Master) -- KDI School: Master of Development Policy, 2022
Keywords: Forest policy--Korea (South); Forest management--Korea (South); Afforestation--Korea (South); Forest ecology--Korea (South)